2006
DOI: 10.1002/app.24708
|View full text |Cite
|
Sign up to set email alerts
|

Development of conductive cotton fabrics for heating devices

Abstract: Recent developments in the area of textiles to make fabrics more functional have led to synthesizing “intelligent fabrics.” This can be achieved by making the fabrics electrically conducting. In the present study it is reported that the cotton fabrics, when impregnated with polypyrrole, achieve enhanced level of conduction. The method of diffusion of pyrrole, followed by polymerization using iron chloride as oxidant, was used. The different levels of conduction were achieved by varying the contents of monomer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 6 publications
1
58
0
1
Order By: Relevance
“…2. The weight increase for the PPy-2h sample was about 46.2%, which is close to that found for the PPy-coated cotton fabrics [40]. The weight increment decreased dramatically when MO was introduced, which was about 23% and 13% for the PPy/MO fabrics with a polymerization time of 1 h and 2 h, respectively.…”
Section: Resultssupporting
confidence: 63%
“…2. The weight increase for the PPy-2h sample was about 46.2%, which is close to that found for the PPy-coated cotton fabrics [40]. The weight increment decreased dramatically when MO was introduced, which was about 23% and 13% for the PPy/MO fabrics with a polymerization time of 1 h and 2 h, respectively.…”
Section: Resultssupporting
confidence: 63%
“…26,27 The methods used in chemical polymerization are as follows: in situ polymerization, 17 two-step polymerization, 19,[22][23][24] emulsion polymerization 9 and vapor phase polymerization. 20,26 The synthesis of PPy on textile substrates is carried out by ferric chloride (FeCl 3 ) and ammonium persulfate (APS).…”
mentioning
confidence: 99%
“…13 Heat generation by conductive polymer-coated textiles has been studied by a number of researchers, 1,7,10,14-19 a brief summary of which is provided here. Bhat et al 14 19 investigated the effect of alkaline weight reduction pretreatment on the heat generation capability of PPy-coated PET fabrics, and found that weight-reduced PET fabrics coated with PPy enjoy a higher heat generation capability as a result of the surface roughness of the treated fibers. Shang et al 10 studied the effect of polymerization on the heat generation capability of PPy-coated PET fabrics.…”
Section: Introductionmentioning
confidence: 98%